How Does Household Portfolio Diversification Vary with Financial Literacy and Financial Advice? - GAUDECKER, HANS‐MARTIN VON (Journal of Finance, 2015)
ABSTRACT Household investment mistakes are an important concern for researchers and policymakers alike. Portfolio underdiversification ranks among those mistakes that are potentially most costly. However, its roots and empirical importance are poorly understood. I estimate quantitatively meaningful diversification statistics and investigate their relationship with key variables. Nearly all households that score high on financial literacy or rely on professionals or private contacts for advice achieve reasonable investment outcomes. Compared to these groups, households with below‐median financial literacy that trust their own decision‐making capabilities lose an expected 50 bps on average. All group differences stem from the top of the loss distribution.